Characteristics of Fracture Patients at the Dr. Mintohardjo Navy Hospital in 2022 - Ellyamurti, Devanti Octavia; Nurrobi, Tjahja (PT Inovasi Pratama Internasional, 2023)
Fractures are discontinuities in bone, joint cartilage, and epiphyseal cartilage that result from direct or indirect trauma. Fractures occur frequently around the globe and in Indonesia, and their incidence is growing annually. According to the World Health Organization (WHO), approximately 13 million people will suffer fractures in 2020. This study aims to determine the demographics of fracture patients and the causes of fractures at Dr. Mintohardjo Navy Hospital in 2022. We conducted a retrospective study of medical records of fracture patients in the Dr. Mintohardjo Navy Hospital, Jakarta, Indonesia in 2022 and this study included 279 participants. According to demographic information, the majority of fracture patients in this study were male, between the ages of 26 and 35, had a bachelor's degree, and were employed as military. In addition, traffic accidents are the leading cause of fractures in patients, with the majority occurring in the clavicle region. In 2022, the majority of fracture patients at Dr. Mintohardjo Navy Hospital were of productive age and male, with the most common cause of fracture being traffic accidents and occurring in the clavicle region.